Dig & Delve into Protein Based Nanoformulations - Shariq, Mohammad; Parveen, Saba; Shamim, Arshiya; Ahsan, Farogh; Kushwaha, Poonam; Mahmood, Tarique (Drug Research, 2020)
Past few decades have emerged as the era of nanotechnology worldwide leading to an extensive research in pharmaceutical science as well as other fields. Nanoformulations have shown a promising future in therapeutics and theronostics. Protein based nanoformulations attracting attention in research as it can be used as therapeutics as well as carrier. Carrier based protein nanoformulatios are capable of accommodating range of therapeutics such as dyes, drugs, contrast agents and inorganic nanoclusters makings its application vast. The nano size of formulation enables it to reach the desired places by some modification. This paper reviewed the various protein based nanoformulation. Human serum albumin, Bovine serum albumin, soy protein isolate, phycocyanin, casein, bromelein, collagen and sericin based nanoformulations are briefly discussed. Various limitations of these proteins can be diminished by developing it in nano form and emerged as promising candidate as carrier as well as therapeutics in drug delivery advancements.
Keywords: protein nanoformulations; nanoformulations; protein therapeutics